Implementing the Arabic language teaching curriculum in linguistic preparation for New Students at the Senior High School Imam Ibn Katsîr in Pekanbaru Riau/ Tanfîzu Manhaj Ta’lîm al-Lughah al-Arabiyah fi al-I’dâd al-Lughawiy ladâ at-Thullâb al-Judad ‘alâ al-Mustawâ al-âliyah bi Ma’had al-Imâm ibn Katsîr Pekanbaru Riau - SISWANDA, LIWAN (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research is a qualitative study. The method used is a qualitative descriptive method. The purpose of this study is to find out how the Arabic language learning method and how to implement the Arabic language learning curriculum at the Islamic boarding school imam ibn kasir pekanbaru riau. This study used primary data sources and secondary data related to the research topic. The data collection methods used in this study are documentation and interviews. The data analysis method used in this study is descriptive qualitative. After the researchers analyzed the research related to the topic, the researcher concluded, that students experienced good language development, which can be seen in terms of language and the average score of the classes that students got. With the ILMA class, students' ability to speak Arabic can be better. Likewise, every year the students who enter the madrasa aliyah imam ibn kasir pekanbaru riau the students continue to grow. The curriculum used is the Arabic curriculum, so to add insight into the Arabic language, the curriculum is very good to be applied in every Islamic boarding school.